Model Strategi Implementasi SMK3L Berbasis ISO 45001, ISO 14001, dan Sistem Manajemen Terintegrasi - Anif Mubarok; Fatma Lestari; Dewi S. Soemarko (Universitas Pahlawan Tuanku Tambusai, 2026)
Abstract The implementation of Occupational Health, Safety, and Environmental Management Systems (OHSEMS) has become increasingly important in supporting organizational performance and sustainability. With the development of ISO 45001 and ISO 14001 standards, many organizations have adopted the Integrated Management System (IMS) approach to improve the effectiveness of occupational safety, health, and environmental management. However, previous studies indicate that the success of OHSEMS implementation is influenced by various organizational, human resource, and control-related factors across different sectors. This study aimed to synthesize implementation models and strategies of OHSEMS based on ISO 45001, ISO 14001, and the Integrated Management System approach. A Systematic Literature Review method following the PRISMA 2020 guidelines was employed. Literature searches were conducted across several international scientific databases, resulting in 47 articles that met the inclusion criteria for analysis. The findings revealed that top management commitment, safety culture, human resource competence, worker participation, communication, risk management, and continual improvement are the most influential factors affecting the success of OHSEMS implementation. Based on the synthesis results, an implementation strategy model consisting of input, process, control, and output components is proposed as a reference for organizations to enhance occupational safety, health, environmental performance, and organizational sustainability.